Effect of chemotherapy on oral health status and salivary alkaline phosphatase among leukemic patients - Al-Rawi, Nadia A; Al-Dafaai, Raya R; Sammi, Mohamad (Journal of Baghdad College of Dentistry, 2013)
Background: Leukemia is a broad term given to a group of malignant diseases characterized by diffuse replacement of bone marrow with proliferating leukocyte precursors. Chemotherapy has been increasingly used to treat malignant conditions. The systemic sequelae as a result of these immunosuppressive techniques induce many oral and dental complications. This study was conducted to evaluate the effect of chemotherapy on oral health status and activity of salivary alkaline phosphates enzyme in patients with acute lymphocytic leukemia. Materials and methods: The study groups included 28 patients with acute lymphocytic leukemia; they were under chemotherapy, aged 20-25 year old. The control group includes healthy subjects matching with study group. Plaque, gingival, calculus and loss of attachment status were recorded. After oral examination, stimulated saliva samples were collected from the subjects (study & control groups) and performed under standard condition following instruction and chemically analyzed for the detection of salivary alkaline phosphates enzyme.Results The study showed higher mean values of plaque index, gingival index, attachment loss and concentration of salivary alkaline phosphates enzyme among leukemic group than control group with statistically high significant differences. Conclusions: It was concluded that patients with acute lymphocytic leukemia have poor oral hygiene and need intense oral hygiene program before, during and after chemotherapy.